Palpable Penile Metastases: A Bizarre Presentation of Rectal Adenocarcinoma - Liza Cholin; Sarah Perz; Furman Mahmood; Saleem Zafar (Case Reports in Urology)
Metastasis to the penis is an uncommon occurrence, with only about 370 cases reported in the literature to date. The majority of the primary tumors are genitourinary in origin. We report on a patient with undiagnosed disseminated rectal adenocarcinoma, who first presented with lesions of the corporal bodies. A review of the literature indicates that corporeal metastasis as an initial presentation of malignancy is an extremely rare occurrence and carries a very poor prognosis.